Assessment of growth, biomass, and carbon sequestration potential of urban tree species in greenbelts - Hina Fatimah; Saba Farooq; Tauseef Anwar; Huma Qureshi; Fasih Hashmi; Tauqeer Ahmad; Naimat Ullah; Mehmooda Munazir; Muhammad Tahir Naseem; Walid Soufan (BMC Plant Biology)
Abstract This study assessed the growth, biomass, and carbon storage potential of four urban tree species—Pinus roxburghii, Broussonetia papyrifera, Jacaranda mimosifolia, and Eucalyptus camaldulensis—in Islamabad’s greenbelts. Sampling was conducted using a quadrat method, covering five sites (F-9, G-8, H-8, I-8, Zero-Point), with 400 trees analyzed. Growth parameters such as diameter at breast height (DBH), height, aboveground biomass (AGB), aboveground carbon density (ACD), belowground carbon density (BCD), basal area (BA), and volume were measured. E. camaldulensis recorded the highest AGB (mean: 2.07 t ha⁻¹, range: 0.05–6.54 t ha⁻¹), ACD (mean: 971.43 t ha⁻¹), and BCD (mean: 233.14 t ha⁻¹), along with the largest DBH (mean: 47.31 cm) and height (mean: 20.10 m). B. papyrifera showed significant carbon storage potential, with mean ACD and BCD values of 373.94 t ha⁻¹ and 89.75 t ha⁻¹, respectively. In contrast, J. mimosifolia displayed the lowest mean AGB (0.2493 t ha⁻¹) but showed considerable variability, with DBH ranging from 7.68 to 59.83 cm. P. roxburghii exhibited moderate values, with a mean AGB of 0.45 t ha⁻¹ and ACD of 212.36 t ha⁻¹. Overall, mean AGB, ACD, and BCD across all species were 0.89 t ha⁻¹, 418.73 t ha⁻¹, and 100.49 t ha⁻¹, respectively, while basal area ranged from 12.07 to 154.94 m² ha⁻¹ (mean: 61.84 m² ha⁻¹). Statistical analysis revealed significant positive correlations among DBH, height, and biomass parameters (p < 0.05). The findings underscore E. camaldulensis as the most effective species for urban carbon sequestration, while B. papyrifera demonstrated positive soil fertility implications. Future research should explore long-term ecological impacts and management strategies for these species in urban landscapes.